2003
DOI: 10.1140/epjc/s2002-01086-1
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation foundation of q-deformed dynamics

Abstract: In the q-deformed theory the perturbation approach can be expressed in terms of two pairs of undeformed position and momentum operators. There are two configuration spaces. Correspondingly there are two q-perturbation Hamiltonians, one originates from the perturbation expansion of the potential in one configuration space, the other one originates from the perturbation expansion of the kinetic energy in another configuration space. In order to establish a general foundation of the q-perturbation theory, two per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…A number of catalysts have been used in one‐pot multicomponent reactions for the synthesis of isoxazol‐5(4 H )‐one scaffolds including boric acid, citric acid, molecular iodine, KI, Ag/SiO 2 , 4‐( N , N‐ dimethylamino) pyridinium acetate, tetrabutylammonium perchlorate/glycine/sodium oxalate, amine‐modified montmorillonite nanoclay, antimony trichloride, mesolite, DABCO functionalized dicationic ionic liquid, nano‐MgO, sodium silicate pentahydrate, citrus fruit juice, pyridinium p‐ toluenesulfonate, cerium chloride heptahydrate, pyridine, nickel (II) acetate and many more . Also, advanced techniques such as microwave heating, grinding, ultrasonic irradiation and visible light in the presence of sodium acetate in aqueous EtOH have also been reported for the preparation of isoxazol‐5(4 H )‐ones, Although many of these protocols suffer from drawbacks and limitations such as low yields/long reaction times, strongly acidic or basic conditions and the use of toxic reagents, stringent reaction conditions, the use of expensive catalyst, multistep synthetic sequence and difficult work up procedures that restrict their scope in practical applications. Considering the above points, we report an efficient and green method for the synthesis of a wide variety of isoxazol‐5(4 H )‐one derivatives via the one‐pot, three‐component process catalyzed by ZnO@Fe 3 O 4 core–shell nanoparticles under aqueous conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of catalysts have been used in one‐pot multicomponent reactions for the synthesis of isoxazol‐5(4 H )‐one scaffolds including boric acid, citric acid, molecular iodine, KI, Ag/SiO 2 , 4‐( N , N‐ dimethylamino) pyridinium acetate, tetrabutylammonium perchlorate/glycine/sodium oxalate, amine‐modified montmorillonite nanoclay, antimony trichloride, mesolite, DABCO functionalized dicationic ionic liquid, nano‐MgO, sodium silicate pentahydrate, citrus fruit juice, pyridinium p‐ toluenesulfonate, cerium chloride heptahydrate, pyridine, nickel (II) acetate and many more . Also, advanced techniques such as microwave heating, grinding, ultrasonic irradiation and visible light in the presence of sodium acetate in aqueous EtOH have also been reported for the preparation of isoxazol‐5(4 H )‐ones, Although many of these protocols suffer from drawbacks and limitations such as low yields/long reaction times, strongly acidic or basic conditions and the use of toxic reagents, stringent reaction conditions, the use of expensive catalyst, multistep synthetic sequence and difficult work up procedures that restrict their scope in practical applications. Considering the above points, we report an efficient and green method for the synthesis of a wide variety of isoxazol‐5(4 H )‐one derivatives via the one‐pot, three‐component process catalyzed by ZnO@Fe 3 O 4 core–shell nanoparticles under aqueous conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The absorption band at 1156 cm 21 was characteristic of the asymmetric stretching of the CAOAC bridge. 23 The band at 1079 cm 21 was attributed to the skeletal vibration involving CAO stretching. 23 The band at 897 cm 21 was assigned to the absorption peaks of b-(1-4)glycosidic bonds in chitosan.…”
Section: Dissolution Of Chitosan In [Imim-cooh]clmentioning
confidence: 99%
“…23 The band at 1079 cm 21 was attributed to the skeletal vibration involving CAO stretching. 23 The band at 897 cm 21 was assigned to the absorption peaks of b-(1-4)glycosidic bonds in chitosan. 24 The FTIR spectra suggested that the important functional groups were still present, and the main polysaccharide chain structure remained after regeneration.…”
Section: Dissolution Of Chitosan In [Imim-cooh]clmentioning
confidence: 99%
“…[1,2,[5][6][7] Many different methods of synthesis are available to produce bimetallic nanoparticles including chemical processes (such as sol-gel, impregnation method, liquid reduction method and others), biological process, physical process, and radiochemical reduction processes. [2,5,[8][9][10][11][12][13] This work demonstrates the production of radioactive BMNPs by water radiolysis using a research nuclear reactor. The reaction of water radiolysis can be defined as shown in Equation 1:…”
Section: Introductionmentioning
confidence: 99%